Digital Ethics and Green Computing for Sustainable Digital Bureaucratic Transformation: Evidence from the West Sulawesi Provincial Plantation Office - Muh. Faizal Thamrin; Muh. Rustan Afandi; Hari Yeni; Irfan (PT. LITERASI SAINS NUSANTARA, 2026)
Digital transformation has become an essential component of public sector reform aimed at improving administrative efficiency, transparency, accountability, and service quality. However, sustainable digital transformation requires not only technological innovation but also the integration of ethical governance and environmentally responsible information technology practices. This study aims to examine the role of digital ethics and green computing in supporting digital bureaucratic transformation at the West Sulawesi Provincial Plantation Office. The study employed a descriptive qualitative case study approach supported by questionnaire data collected from 60 civil servants using purposive sampling, complemented by documentary analysis of relevant government regulations and institutional documents. The data were analyzed using the interactive qualitative analysis model consisting of data condensation, data display, and conclusion drawing. The findings indicate that digital ethics strengthens transparency, accountability, information security, and responsible technology utilization, thereby enhancing organizational trust and supporting effective digital governance. Furthermore, green computing contributes to bureaucratic efficiency through paperless administration, digital document management, efficient utilization of information technology resources, and environmentally sustainable administrative practices. The integration of digital ethics and green computing was found to reinforce digital bureaucratic transformation by improving organizational effectiveness, administrative responsiveness, and public service quality. These findings suggest that sustainable digital government depends not only on technological capability but also on the institutional integration of ethical governance and environmentally responsible digital practices. The study provides practical recommendations for local governments to strengthen digital governance policies, improve employees' digital competencies, and expand sustainable technology initiatives in support of modern public administration.